ترسيخ أخلاقيات الأعمال كآلية لتفعيل عملية صنع القرار بالمؤسسات الإقتصادية - مهديد, فاطمة الزهراء (Recherches économiques et managériales; Vol. 21 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES, 2018)
هدفت هذه الدراسة إلى التعرف على تصورات الأفراد العاملين في مؤسسات ميدان الدراسة نحو مدى تأثير أخلاقيات الأعمال على فعالية صنع القرار، ولتحقيق أهداف الدراسة أجرت الباحثة مسحا ميدانيا على عينة من المؤسسات الاقتصادية بولاية برج بوعريريج، من خلال تصميم استمارة، حيث تكون مجتمع الدراسة من جميع العمال والإداريين المتواجدين في مختلف مديريات ودوائر المؤسسات والبالغ عددهم 193 ، وقد تم اختيار العينة التي بلغ عددها 49 مفردة ، وفي ضوء ذلك جرى جمع وتحليل البيانات واختبار الفرضيات باستخدام الحزمة الإحصائية للعلوم الاجتماعية SPSS . وتوصلت الدراسة إلى عدة نتائج أهمها وجود أثر ذو دلالة إحصائية لأخلاقيات الأعمال على أبعاد فعالية صنع القرار ( جودة القرار، قبول القرار، وقت اتخاذ القرار وسهولة تنفيذ القرار ) ، ووجود علاقة ارتباط ذات دلالة معنوية بين المتغير المستقل أخلاقيات الأعمال والمتغير التابع فعالية صنع القرار بأبعاده . الكلمات المفتاحية : أخلاقيات الأعمال صنع القرار، فعالية صنع القرار، المؤسسة الاقتصادية . Abstract: This study aimed to identify the perceptions of working individuals about the reality of Business ethics prevailing in their enterprises, and its impact on the effectiveness of decision-making, Achieving this study's objectives the researcher has conducted a survey on Economic Enterprises Bordj Bou Arreridj , by designing a questionnaire , where the study population consisted of all workers and administrators in various directorates and departments of enterprises, totaling 193, and the choosing sample consisted of 49 individuals,the collecting and analyzing data and testing hypotheses process has been carried out using the Statistical Package for Social Sciences (SPSS). The study reached an important result, which is, Business ethics statistically have significant effects on the dimensions of the effectiveness of the decision-making (the quality of the decision, acceptation of decision, the time of decision-making and the ease of implementation of the resolution). And the presence of significant a significant correlation between the independent variable business ethics dependent variable effectiveness of decision-making Key words : Business Ethics, Decision-Making, the effectiveness of decision-making, economic enterprises